Internalization of Religious Moderation Values Based on Discovery Learning in Indonesian Language Materials at Madrasah Ibtidaiyah - Ihwanah, Al; Elhefni; Saputra, Agra Dwi; Wulandari, Bintang; Sari, Tri Mayang (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2025)
This study aims to explore the potential application of the discovery learning method in internalizing the values of religious moderation in Indonesian language learning at Madrasah Ibtidaiyah Negeri Ogan Ilir. Motivated by the importance of religious moderation in the context of socio-cultural diversity in Indonesia, this study uses a qualitative approach with data taken from interviews, observations, and documentation. Data validity was tested using source triangulation, technique triangulation, and method triangulation. The data analysis techniques applied include initial data processing, coding, and data analysis. The results showed that the application of the discovery learning method was effective in improving students' understanding of the values of religious moderation as well as their active involvement in the learning process. Students are trained to appreciate diversity and develop tolerant and empathetic attitudes during interactive learning activities. In addition, the study highlighted the need to strengthen an inclusive curriculum and provide teachers with training to integrate religious moderation into their teaching consistently. The results are expected to contribute to the development of better character education in Indonesia and recommend the application of active learning methods to create a generation that is tolerant and inclusive of differences. The study suggests that further exploration be conducted in various madrasahs to understand the long-term impact of this method.